2021
DOI: 10.1590/1809-4392202003702
|View full text |Cite
|
Sign up to set email alerts
|

Strong El Niño reduces fruit production of Brazil-nut trees in the eastern Amazon

Abstract: The Brazil-nut tree (Bertholletia excelsa) is native to the Amazon rainforest, and its fruit production varies naturally with climatic conditions. Our aim was to evaluate the temporal variation in Brazil-nut production associated with climatic variables, including the strong El Niño of 2015/2016. The study was carried out in two 9-ha permanent plots in the northeastern Brazilian Amazon from 2007 to 2018: one in forest (12-year monitoring) and the other in savannah/forest transition (eight years). Overall, we m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Regarding temperature, it was possible to observe a significant influence of temperature measurements from 1 year before seed collection. Similar results were observed by Pastana et al [18]. These authors identified a negative relationship between Brazil nut production and temperature anomalies occurring in the third quarter before harvest in the Sul do Amapá mesoregion.…”
Section: Influence Of Climate Variation On Brazil Nut Production In T...supporting
confidence: 88%
See 2 more Smart Citations
“…Regarding temperature, it was possible to observe a significant influence of temperature measurements from 1 year before seed collection. Similar results were observed by Pastana et al [18]. These authors identified a negative relationship between Brazil nut production and temperature anomalies occurring in the third quarter before harvest in the Sul do Amapá mesoregion.…”
Section: Influence Of Climate Variation On Brazil Nut Production In T...supporting
confidence: 88%
“…However, seed production in other mesoregions may be influenced by precipitation. This was evident in the Sul do Amapá mesoregion, where an association was observed between low precipitation and reduced production [18], and in the Sul Amazonense (AM) mesoregion, where a relationship was noted between excessive precipitation and Brazil nut tree mortality [48], potentially reducing fruit production.…”
Section: Influence Of Climate Variation On Brazil Nut Production In T...mentioning
confidence: 99%
See 1 more Smart Citation
“…The climate in the region is classified as tropical savanna (Aw) and tropical monsoon (Am) by the Köppen classification (Alvares et al, 2013; Peel et al, 2007). The average annual temperature is 25°C, and average annual precipitation is 2300 mm, with rainy period from January to July and dry period from August to December (Pastana et al, 2021). The altitude varies around 150 m a.s.l.…”
Section: Methodsmentioning
confidence: 99%
“…This reduction in production areas could cause a 4.2% decrease in national cocoa production and affect the income of almost 9,000 families. Likewise, Pastana et al (2021), evaluating the effect of the 2015/2016 El Niño on the annual production of Brazil nuts (B. excelsa) in the Rio Cajari Extractive Reserve (Amapá), found a strong relationship between the reduction in precipitation and the increase in temperature with the decrease in Brazil nut production. The authors report that the reduction in production and the consequent low supply of Amazonian nuts in a strong market with rising prices led to invasions and conflicts in extractive units.…”
Section: Challenges For the Sustainable Management Of Natural Resourc...mentioning
confidence: 99%